1996
DOI: 10.1021/ja952796l
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Vinyl Cations by β-Silicon:  A Quantitative Mass Spectrometric Study

Abstract: The stabilization afforded a vinyl cation by a β-(CH3)3Si substituent has been determined by measuring in a high-pressure mass spectrometer the thermodynamic data for the association of three alkynes (RCCR‘) with (CH3)3Si+ and with the proton. The measured −ΔH° (kcal mol-1) and −ΔS° (in parentheses, cal K-1 mol-1) values for the reaction (CH3)3Si+ + RCCR‘ ⇄ (CH3)3Si·C(R)CR‘+ are as follows:  1-hexyne (R = H, R‘ = n-C4H9) 25.9 ± 1.5 (19.1 ± 0.2), 2-hexyne (R = CH3, R‘ = n-C3H7) 28.8 ± 1.4 (25.5 ± 0.3), and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…aryl groups, the participation of the silicon in the stabilization is lower when compared to -alkyl substituents (Scheme 3). 31 It was discovered that ,-silyl disubstituted vinyl cations 41 are surprisingly stable in solution and as anhydrous salts with tetrakis(pentafluorophenyl)borate as counterion. Their NMR, 32 X-ray diffraction, 33 and IR spectroscopy 34 studies revealed further correlation between cation stabilization from an -aryl substituent and hyperconjugation from the -silyl group (Scheme 4).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…aryl groups, the participation of the silicon in the stabilization is lower when compared to -alkyl substituents (Scheme 3). 31 It was discovered that ,-silyl disubstituted vinyl cations 41 are surprisingly stable in solution and as anhydrous salts with tetrakis(pentafluorophenyl)borate as counterion. Their NMR, 32 X-ray diffraction, 33 and IR spectroscopy 34 studies revealed further correlation between cation stabilization from an -aryl substituent and hyperconjugation from the -silyl group (Scheme 4).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…Once again, the formation of neutral silylated products is in favor of an ionic silylated intermediate which can be depicted either as a bridged species or as a β−silyl substitued vinyl cation. The formation of the silylation product of acetylene itself, the parent alkyne, is remarkable, in view of the inability to observe the silylated adduct ion in high-pressure mass spectrometry . This contrasting behavior is probably the result of the different pressure range used by the two techniques.…”
Section: Resultsmentioning
confidence: 99%
“…This geometrical bias can be attributed to the β-silicon effect to overlap the C(1)–Si and empty p-orbital of a carbocationic C(2) atom . This alignment will accordingly decrease the dihedral angle of Si–C(1)–C(2) relative to that of C(3)–C(1)–C(2), thus favoring the borohydride attack to ketene iminium species via the sterically more accessible anti -addition path.…”
mentioning
confidence: 99%